Physical Therapies for Psychosomatic Symptoms and Quality of Life Induced by Aromatase Inhibitors in Breast Cancer Patients: A Systematic Review and Meta-Analysis - Zhu, Xue-Ying; Li, Zhong; Chen, Cong; Feng, Ru-Li; Cheng, Bai-Ru; Liu, Ruo-Yi; Wang, Rui-Ting; Xu, Li; Wang, Yue; Tao, Xin; Zhao, Peng (Frontiers in Oncology, 2021)
Objective: To evaluate the effects of Physical Therapies (PTs) on improvement in psychosomatic symptoms and quality of life (QOL) in breast cancer patients. Data Sources: Seven databases (MEDLINE, EMBASE, Cochrane CENTRAL, China National Knowledge Infrastructure, Wangfang, VIP, and China Biology Medicine disc databases) were systematically searched from the database inception through May 18, 2021. Study Selection: Randomized controlled trials (RCTs) which compared acupuncture or exercise with a sham control or usual care for the treatment of aromatase inhibitors (AIs)-related psychosomatic symptoms and QOL. Results: Eleven RCTs (with 830 patients) were included in the systematic review, and data from 10 RCTs (with 798 patients) were used in the meta-analysis. The result showed acupuncture significantly reduced worst pain scores (P < 0.00001, I2 = 83.5%) [SMD = −0.81, 95% CI [−1.51, −0.11]], but the effect of exercise therapies was not significant in overall change in worst pain scores (P =0.006, I2 = 72.3%) [SMD = −0.30, 95% CI [−0.76, 0.16]]. Both acupuncture and exercise resulted in little to no difference in overall change in HADS-A subscale (P = 0.026＜0.05, I2 = 79.8%) [WMD = −0.21, 95% CI [−3.44, 3.03]], PSQI subscale (P = 0.488, I2 = 0%) [WMD = 0.98, 95% CI [−0.57, 2.53]] and FACIT-Fatigue subscale (P = 0.022＜0.05, I2 = 81.0%) [WMD = 1.6, 95% CI [−5.75, 8.94]]. Exercise (compared with usual care) was associated with improving overall change in health-related QOL (subscales of SF-36 tool) (P = 0, I2 = 72.1%) [WMD = 7.97, 95% CI [5.68, 10.25]], overall change in cancer-specific QOL (subscales of FACT-G tool) P = 0.304, I2 = 16%) [WMD = 1.16, 95% CI [0.34, 1.97]]. Conclusions and Relevance: This systematic review and meta-analysis suggested that based on moderate-level evidence, acupuncture was associated with significant reductions in pain intensity and exercise, might improve QOL in breast cancer patients treated with AIs. However, on some of psychosomatic symptoms such as anxiety, sleep disturbance and fatigue, acupuncture and exercise training didn't result in significant improvement.